Strategic Diversification into Sustainability Consulting: an Internal–External Fit Analysis of Premysis Consulting - Tasya, Adella (Riviera Publishing, 2026)
This research examines Premysis Consulting’s strategic diversification into sustainability and ESG (Environmental, Social, and Governance) consulting using an internal–external fit approach. The study explores how the firm’s ISO-based consulting expertise can be leveraged to enter Indonesia’s emerging ESG market, driven by POJK 51/2017 and increasing stakeholder expectations. A qualitative exploratory method was applied, incorporating internal interviews, six external client discussions, and a focused group discussion (FGD). The PESTEL and VRIN–RBV analyses reveal that while Premysis possesses valuable assets such as strong client trust, a structured methodology, and regulatory competence, the firm faces capability gaps in ESG-specific technical skills, digital tools, and innovation diffusion. Thematic findings identify four market segments: Compliance-Oriented, Transformation-Focused, Mid-Sized/Underserved, and Innovation-Oriented clients. Among these, the Transformation-Focused and Mid-Sized segments present the most strategic opportunities. The study recommends a hybrid business-level strategy, combining focused differentiation for transformation clients and cost leadership for SMEs. ESG diversification is deemed viable if supported by talent upskilling, digital integration, and partnership-based positioning. This research contributes to the sustainability consulting literature by demonstrating how internal–external alignment enables consulting firms to evolve from compliance-driven services toward strategic ESG advisory.